Method for catalytically degrading o-dichlorobenzene by using in-situ synthesized noble metal-based catalyst

The precious metal-based catalysts synthesized in situ solves the problem of o-dichlorobenzene contamination in the exhaust gas produced during the preparation of XDI by urea method, and achieves efficient and environmentally friendly degradation effect, converting o-dichlorobenzene into harmless substances and by-products Low yield, suitable for industrial applications.

CN119425774APending Publication Date: 2025-02-14BEIJING UNIV OF CHEM TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411697507.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the preparation of isophthalic dimethyl isocyanate (XDI) by urea method, the produced exhaust gas contains the non-biodegradable harmful pollutant ortho-dichlorobenzene, which leads to environmental pollution and human health hazards. The existing catalysts have poor ability to catalyze oxidize chlorine-containing aromatics at low temperatures and have low selectivity, which cannot meet the requirements of efficient and environmentally friendly degradation of o-dichlorobenzene in industrial exhaust gases.

Method used

Using in-situ synthesized noble metal-based catalyst, the noble metal complex solution is formed by dropping ethylenediamine into the noble metal salt solution, and mixed with aluminum source, silicon source and tin salt, and crystallization, washing, drying and Catalysts are prepared by calcining and other steps. This method can achieve 100% conversion of ortho-dichlorobenzene in industrial exhaust gases within a temperature range of 350 to 400°C, and the by-product yield is less than 5%.

Benefits of technology

It has achieved a green, environmentally friendly and efficient degradation of the exhaust gas emission problem of ortho-dichlorobenzene in the industry, converted it into CO2, H2O and HCl, with low by-product yield and simple catalyst operation, making it suitable for industrial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005152458350000041
    Figure BDA0005152458350000041
  • Figure BDA0005152458350000061
    Figure BDA0005152458350000061
  • Figure BDA0005152458350000072
    Figure BDA0005152458350000072
Patent Text Reader

Abstract

The invention discloses an in-situ synthesized noble metal-based molecular sieve catalyst and a method for catalytically degrading o-dichlorobenzene in industrial tail gas. According to the catalyst, an MFI molecular sieve is used as a carrier, noble metals such as ruthenium, palladium, platinum and rhodium are used as active components, and a second component tin is doped to assist in improving the stability and product selectivity of the catalyst. When the reaction temperature of the catalyst is 350-400 DEG C, o-dichlorobenzene in industrial tail gas can be completely degraded to generate CO2, H2O and HCl, and the yield of by-products (Cl2 and polychlorobenzene) is less than 5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of catalytic degradation, and in particular to a method for catalytic degradation of o-dichlorobenzene using an in-situ synthesized noble metal-based catalyst. Background Art

[0002] Meta-phenylenediisocyanate (XDI) is a special isocyanate with a broad market space. It is widely used in optical resins, coatings and adhesives, new energy materials and other fields. At present, there are two main methods for preparing XDI: phosgene method and non-phosgene method. Phosgene method is a traditional method for preparing XDI, but this method has major problems in terms of safety and environmental protection. Non-phosgene method is the current research hotspot and development direction in the field of XDI preparation. Among them, the urea method for preparing XDI is a synthetic method with development potential. By selecting suitable catalysts and optimizing reaction conditions, efficient and environmentally friendly XDI production can be achieved. However, in the process of preparing XDI by urea method, tail gas pollutants containing o-dichlorobenzene (O-DCB) will be produced, which will cause harm to the atmospheric environment and human health.

[0003] Studies have shown that repeated or long-term exposure to o-dichlorobenzene may cause skin defatting, dryness or cracking. If ingested, o-dichlorobenzene can cause kidney and liver damage. The substance may also cause damage to the central nervous system, liver, kidneys and blood system. The World Health Organization's International Agency for Research on Cancer has included o-dichlorobenzene in the list of Class 3 carcinogens. o-dichlorobenzene is a non-biodegradable organic compound that causes significant harm to the environment. On the one hand, o-dichlorobenzene is soluble in water and can pollute water bodies. On the other hand, o-dichlorobenzene is highly volatile and can be easily released into the atmosphere, causing a decrease in air quality. o-dichlorobenzene is toxic to aquatic organisms and other members of the ecosystem, and will further disrupt the ecological balance. Therefore, how to quickly, efficiently and safely eliminate o-dichlorobenzene in industrial exhaust gas is very important for human health and ecological environment protection.

[0004] In the prior art, the technologies for treating chlorinated aromatic hydrocarbon pollutants such as o-dichlorobenzene mainly include adsorption and catalytic oxidation. Among them, the adsorption method can only enrich the pollutant molecules, but cannot degrade the pollutants. The catalytic oxidation method is considered to be the most promising means for removing chlorinated aromatic hydrocarbon pollutants because of its advantages such as low combustion temperature, high treatment efficiency and good safety. The key lies in the development of catalysts. In recent years, precious metal catalysts with high catalytic activity at low temperature have attracted extensive attention from scholars at home and abroad. Patent CN118698588A provides a Cu-Ce composite metal oxide for degrading chlorinated aromatic hydrocarbon organic pollutants. The invention finally obtains a Cu-Ce composite metal oxide with a mesoporous structure by calcination. The catalyst is ground or processed into a shape and mixed with chlorinated aromatic hydrocarbon organic pollutants or placed in an environment containing chlorinated aromatic hydrocarbon organic pollutants to achieve higher catalytic activity. However, compared with precious metal catalysts, transition metal oxide catalysts have poorer ability to catalytically oxidize chlorinated aromatic hydrocarbons at low temperatures and lack selectivity. Patent CN110433800A discloses the preparation of a supported ruthenium catalyst with a crystal face effect. By preparing a TiO2 carrier that exposes a specific (001) crystal face, regulating the location of Ru on the TiO2 (001) crystal face, and utilizing the strong interaction between Ru and the carrier, a Ru / TiO2 catalyst with a functionalized nanostructure is assembled to achieve catalytic degradation of chloroaromatic hydrocarbons. However, when oxides are used as carriers, their low specific surface area results in fewer exposed active sites and poor degradation efficiency of chloroaromatic hydrocarbons. Patent CN118206437A discloses a method for synthesizing oxides by catalyzing olefin oxidation using a molecular sieve-supported metal catalyst. The method uses precious metal Pd as an active component and zeolite molecular sieve as a carrier. Since the zeolite molecular sieve has a regular topological structure, it has an efficient enrichment ability for substrate molecules, accelerates the adsorption conversion of substrate molecules, and improves the conversion rate. However, the active components of the supported catalyst are unevenly dispersed on the carrier, resulting in low catalytic activity and selectivity. The above existing disclosed catalysts still cannot meet the requirements of efficient and environmentally friendly degradation of o-dichlorobenzene in industrial tail gas. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention provides a preparation method of an in-situ synthesized precious metal-based catalyst and its application, which mainly solves the tail gas emission problem of o-dichlorobenzene in the process of synthesizing XDI by urea method. The catalyst prepared by the method can efficiently and environmentally degrade the o-dichlorobenzene component in industrial waste gas and convert it into CO2, H2O and HCl, while achieving a by-product yield of less than 5%.

[0006] A method for in-situ synthesis of a noble metal-based catalyst of the present invention is characterized by comprising the following steps:

[0007] Preparation of in-situ synthesized precious metal catalysts: (1) dropping an excess of ethylenediamine into a precious metal salt solution, stirring until the solution becomes clear, and forming a precious metal complex solution; (2) mixing an aluminum source and a silicon source, and then sequentially adding tetrapropylammonium hydroxide (TPAOH) and water (H2O), stirring sufficiently at room temperature, adding the precious metal complex solution to obtain a catalyst synthesis mother liquor, transferring the mother liquor to an autoclave, crystallizing at a certain temperature, filtering the obtained solid sample, and washing it with deionized water and ethanol for 5 times respectively; (3) then transferring the mother liquor to a vacuum oven for drying for a certain period of time, and then transferring the mother liquor to a muffle furnace for calcination;

[0008] Or prepare an in-situ synthesized precious metal catalyst doped with tin as the second metal component: (1) add an excess of ethylenediamine to a precious metal salt solution, stir until the solution becomes clear, and form a precious metal complex solution; (2) mix an aluminum source and a silicon source, then add tetrapropylammonium hydroxide (TPAOH) and water (H2O) in sequence, stir well at room temperature, and then add the precious metal complex solution obtained in step (1) to obtain a catalyst synthesis mother liquor; (3) dissolve a tin salt in a certain amount of ethylene glycol to form a tin solution, dissolve thiourea (CH4N2S) in a certain amount of ethylene glycol solution to form a thiourea solution, and fully mix the tin solution and the thiourea solution to form a transparent solution; (4) then add the transparent solution obtained in step (3) to the catalyst synthesis mother liquor obtained in step (2), and then transfer it to an autoclave and crystallize it at a certain temperature for a period of time; filter and obtain a solid sample and wash it with deionized water and ethanol for 5 times respectively; (5) then transfer it to a vacuum oven to dry for a certain period of time, and then transfer it to a muffle furnace for calcination.

[0009] In the above preparation method, the noble metal salt includes one or more of nitrate, chloride and sulfate.

[0010] The noble metal element includes one or more of palladium (Pd), platinum (Pt), and ruthenium (Ru).

[0011] The concentration of the noble metal complex solution is 0.001-0.04 mol / L.

[0012] The molar ratio of the noble metal to ethylenediamine in the noble metal complex solution is noble metal:ethylenediamine=1:2-10.

[0013] The aluminum source is aluminum chloride (AlCl3), aluminum sulfate (Al2(SO4)3), sodium aluminate (NaAlO2), aluminum isopropoxide (C9H 21 AlO3) or more.

[0014] The silicon source is one or more of SiO2, silicic acid, and tetraethyl orthosilicate (TEOS).

[0015] The molar ratio of each component in the catalyst synthesis mother liquid is Si:Al=1:0.02-0.2, and more preferably Si:Al=1:0.03-0.1; Si:TPAOH=1:0.5-1.5, Si:H2O=1:10-25;.

[0016] The molar ratio of tin to ethylene glycol in the tin solution is tin:ethylene glycol=1:10-25, the molar ratio of thiourea to ethylene glycol in the thiourea solution is thiourea:ethylene glycol=1:5-15, and the molar ratio of tin to thiourea is tin:thiourea=1:1-10;

[0017] The crystallization temperature is 130-220° C., and the crystallization time is 10-72 hours.

[0018] The calcination temperature is 450-700° C., and the calcination time is 1-10 hours.

[0019] The amount of the noble metal in the catalyst after final calcination is 0.1-5wt%, the amount of the second component tin element is 0.1-2wt%, and the molar ratio of tin element to noble metal is more preferably tin:noble metal=1:0.1-1.

[0020] There are no special requirements for the stirring time, stirring temperature, drying temperature and drying time in the above steps. The stirring temperature is, for example but not limited to, 20 to 60°C; the stirring time is, for example but not limited to, 2 to 48 hours; the drying temperature is, for example but not limited to, 80 to 120°C, and the drying time is, for example but not limited to, 12 to 36 hours.

[0021] The above-mentioned in-situ synthesized noble metal-based catalyst is used to degrade o-dichlorobenzene in industrial tail gas. Within the temperature range of 350 to 400° C., 100% conversion of o-dichlorobenzene pollutants in industrial tail gas can be achieved and the yield of by-products (Cl2, polychlorobenzenes) is less than 5%.

[0022] The beneficial effects of the present invention are as follows: the catalyst provided by the present invention can achieve the problem of tail gas emission of o-dichlorobenzene in industrial degradation in a green, environmentally friendly and efficient manner, convert o-dichlorobenzene components into CO2, H2O and HCl, and achieve a by-product yield of less than 5%. The method for preparing the catalyst is simple to operate, harmless to the human body and the environment, convenient for industrial application, and has good application prospects. DETAILED DESCRIPTION

[0023] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments. These embodiments do not limit the scope of the present invention in any way.

[0024] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0025] Catalyst performance test method:

[0026] 150 mg of the catalyst was pelletized and loaded into a quartz reaction tube with an inner diameter of 6 mm. The total gas flow rate was 100 mL / min, the O-DCB concentration was 1000 ppm, the O2 content was 10%, (N2 was the balance gas), and the mixed gas volume space velocity was 40000 h -1 The catalytic degradation of O-DCB is carried out under the conditions of 250-500°C. When the reaction temperature is within the range of 250-500°C, a sampling test and analysis is performed every 50°C by using a mass spectrometer-chromatography device.

[0027] The analysis method of Cl2 and HCl in the gas is: absorb the reactor outlet gas with (12.5mmol / L) NaOH aqueous solution for 0.5 hours each time, and then use 0.01mol / L ammonium ferrous sulfate and N,N-diethyl-p-phenylenediamine as indicators to titrate and obtain the Cl2 concentration. - The concentration is detected by a chloride ion selective electrode.

[0028] The O-DCB conversion rate and product yield were calculated by the following formula:

[0029]

[0030] Where: [O-DCB] in is the inlet concentration of o-dichlorobenzene; [O-DCB] out is the outlet concentration of o-dichlorobenzene; [CO2], [HCl], [Cl2] and [C x H y Cl z ] are the outlet concentrations of carbon dioxide, hydrogen chloride, chlorine and polychlorinated benzenes, respectively.

[0031] Example 1

[0032] 0.03 mL of ethylenediamine (RuCl3: NH2CH2CH2NH2 (ethylenediamine) = 1:10) was added dropwise to 18.53 mL of 0.0024 mol / L RuCl3 solution, and stirred until the solution became clear to obtain a noble metal complex solution. 0.295 g of NaAlO2 and 20 mL of TEOS were mixed (TEOS: NaAlO2 = 1:0.037), and then 14.68 mL of TPAOH (TEOS: TPAOH = 1:0.75) and 29.59 mL of H2O (TEOS: H2O = 1:17.13) were added in sequence. After being stirred at room temperature for 6 hours, the noble metal complex solution was added to obtain a catalyst synthesis mother solution. 0.32 mL of 0.9 mol / L SnCl4 ethylene glycol solution (SnCl4: (CH2OH)2 (ethylene glycol) = 1:20) was mixed with 0.34 mL of 1.7 mol / L thiourea (CH4N2S) ethylene glycol solution (CH4N2S: (CH2OH)2 = 1:10) to form a transparent solution (SnCl4: CH4N2S = 1:2), and the solution was added to the catalyst synthesis mother liquor (SnCl4: RuCl3 = 1:0.15), and then transferred to an autoclave. Crystallize at 170°C for 2 days. The obtained sample was washed 5 times with deionized water and ethanol respectively. Then it was transferred to an 80°C vacuum oven and dried overnight. The dried sample was calcined in a muffle furnace at 550°C and a heating rate of 5°C / min for 6 hours. Example 1 RuSn@ZSM-5 bimetallic catalyst was obtained.

[0033] Example 2

[0034] 0.03 mL of ethylenediamine (RuCl3: NH2CH2CH2NH2 (ethylenediamine) = 1:10) was added dropwise to 18.53 mL of 0.0024 mol / L RuCl3 solution, and the solution was stirred until it became clear to obtain a noble metal complex solution. 0.295 g of NaAlO2 and 20 mL of TEOS were mixed (TEOS: NaAlO2 = 1:0.037), and then 14.68 mL of TPAOH (TEOS: TPAOH = 1:0.75) and 29.59 mL of H2O (TEOS: H2O = 1:17.13) were added in sequence. After being stirred at room temperature for 6 hours, the noble metal complex solution was added to obtain the catalyst synthesis mother liquor, which was transferred to an autoclave and crystallized at 170°C for 2 days. The obtained sample was washed 5 times with deionized water and ethanol, respectively. Then it was transferred to a vacuum oven at 80°C and dried overnight, and the dried sample was calcined in a muffle furnace at 550°C with a heating rate of 5°C / min for 6 hours to obtain the Ru@ZSM-5 catalyst of Example 2.

[0035] Example 3

[0036] 0.03 mL of ethylenediamine (H2PtCl6: NH2CH2CH2NH2 (ethylenediamine) = 1:10) was added dropwise to 4.33 mL of 0.01 mol / L H2PtCl6 solution, and stirred until the solution became clear to obtain a noble metal complex solution. 0.295 g of NaAlO2 and 20 mL of TEOS were mixed (TEOS: NaAlO2 = 1:0.037), and then 14.68 mL of TPAOH (TEOS: TPAOH = 1:0.75) and 29.59 mL of H2O (TEOS: H2O = 1:17.13) were added in sequence. After being stirred at room temperature for 6 hours, the noble metal complex solution was added to obtain the catalyst synthesis mother liquor, which was transferred to an autoclave and crystallized at 170°C for 2 days. The obtained sample was washed 5 times with deionized water and ethanol, respectively. Then it was transferred to a vacuum oven at 80°C and dried overnight, and the dried sample was calcined in a muffle furnace at 550°C with a heating rate of 5°C / min for 6 hours to obtain the Example 3 Pt@ZSM-5 catalyst.

[0037] Example 4

[0038] 0.05 mL of ethylenediamine (PdCl2: NH2CH2CH2NH2 (ethylenediamine) = 1:10) was added dropwise to 2.64 mL of 0.03 mol / L PdCl2 solution, and stirred until the solution became clear to obtain a noble metal complex solution. 0.295 g of NaAlO2 and 20 mL of TEOS were mixed (TEOS: NaAlO2 = 1:0.037), and then 14.68 mL of TPAOH (TEOS: TPAOH = 1:0.75) and 29.59 mL of H2O (TEOS: H2O = 1:17.13) were added in sequence. After being stirred at room temperature for 6 hours, the noble metal complex solution was added to obtain the catalyst synthesis mother liquor, which was transferred to an autoclave and crystallized at 170 ° C for 2 days. The obtained sample was washed 5 times with deionized water and ethanol, respectively. Then it was transferred to a vacuum oven at 80°C and dried overnight, and the dried sample was calcined in a muffle furnace at 550°C with a heating rate of 5°C / min for 6 hours to obtain the Pd@ZSM-5 catalyst of Example 4.

[0039] Comparative Example

[0040] Mix 0.295g NaAlO2 and 20ml TEOS (TEOS:NaAlO2=1:0.037), then add 14.68mL TPAOH (TEOS:TPAOH=1:0.75) and 29.59mL H2O (TEOS:H2O=1:17.13) in sequence. Stir well at room temperature for 6 hours, transfer it to an autoclave, and crystallize it at 170°C for 2 days. The obtained samples were washed 5 times with deionized water. Then transfer it to a vacuum oven at 80°C and dry overnight. The dried sample was calcined in a muffle furnace at 550°C and a heating rate of 5°C / min for 6 hours. The MFI molecular sieve was obtained.

[0041] Add MFI molecular sieve to 40mL deionized water, stir evenly at a speed of 500-600r / min, then dropwise add 18.53mL of RuCl3 solution with a concentration of 0.0024mol / L, and stir at room temperature for 6h to mix evenly. Then perform rotary evaporation at 80℃ and dry at 100℃ for 12h. After drying, calcine at 550℃, with a heating rate of 5℃ / min for 6 hours. Obtain comparative Ru / ZSM-5 catalyst.

[0042] Experimental Results

[0043] Table 1 o-dichlorobenzene conversion data of Examples 1 to 4 and Comparative Examples

[0044]

[0045]

[0046] Table 2 Product yield data of Examples 1 to 4 and Comparative Example when the reaction temperature is 350°C

[0047]

[0048] Table 3 Product yield data of Examples 1 to 4 and Comparative Examples when the reaction temperature is 400°C

[0049]

[0050] Table 1 shows the data of the conversion rate of o-dichlorobenzene catalyzed by different catalysts under the same conditions in Examples 1 to 4 and Comparative Examples. Table 2 shows the product yield data of each catalyst when the reaction temperature is 350°C. Table 3 shows the product yield data of each catalyst when the reaction temperature is 400°C.

[0051] It can be seen from the data of Examples 1 to 4 and the comparative example that the in situ synthesized precious metal-based catalyst can completely convert o-dichlorobenzene at 350 to 400° C., and the yield of by-products (Cl2, polychlorobenzenes) is much lower than that of the supported precious metal-based catalyst. Therefore, the in situ synthesized precious metal-based catalyst has better o-dichlorobenzene degradation performance.

[0052] From the data of Example 2, Example 3 and Example 4, it can be seen that the activity order of each catalyst at the same temperature is: Example 2> Example 3> Example 4, among which Example 2 can achieve a conversion rate of more than 90% at 350°C and a by-product (Cl2, polychlorobenzenes) yield of less than 3%. This shows that the efficiency of the in-situ synthesized ruthenium-based catalyst in catalyzing the degradation of o-dichlorobenzene is significantly stronger than that of the in-situ synthesized platinum and palladium-based catalysts.

[0053] Comparing the data of Example 1 and Example 2, under the same other conditions, Example 1 achieves 100% o-dichlorobenzene degradation efficiency at 350°C, and the HCl yield is as high as 100%, and no by-products (Cl2, polychlorobenzenes) are generated. However, Example 2 only reaches 100% o-dichlorobenzene conversion at 400°C, and there are by-products. Therefore, the bimetallic catalyst doped with tin can further improve the degradation performance of o-dichlorobenzene.

[0054] The above is a detailed description of the embodiments of the present invention, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.

[0055] Any matters not described in the present invention are applicable to the prior art.

Claims

1. A method for in-situ synthesis of a noble metal-based catalyst, characterized in that: The following steps are involved: (1) adding an excess of ethylenediamine to a noble metal salt solution and stirring until the solution becomes clear to form a noble metal complex solution; (2) mixing an aluminum source and a silicon source, and then sequentially adding tetrapropylammonium hydroxide (TPAOH) and water (H2O), stirring sufficiently at room temperature, adding the noble metal complex solution to obtain a catalyst synthesis mother liquor, transferring the mother liquor to an autoclave, crystallizing at a certain temperature, filtering the obtained solid sample, and washing it with deionized water and ethanol for 5 times respectively; (3) Then it is transferred to a vacuum oven to dry for a certain period of time, and then transferred to a muffle furnace for calcination.

2. A method for in-situ synthesis of a noble metal-based catalyst, characterized in that: The invention discloses an in-situ synthesis precious metal catalyst doped with tin as a second metal component, which specifically comprises the following steps: (1) dropping an excess of ethylenediamine into a precious metal salt solution, stirring until the solution becomes clear, and forming a precious metal complex solution; (2) mixing an aluminum source and a silicon source, and then sequentially adding tetrapropylammonium hydroxide (TPAOH) and water (H2O), stirring sufficiently at room temperature, and then adding the precious metal complex solution obtained in step (1) to obtain a catalyst synthesis mother liquor; (3) dissolving a tin salt in a certain amount of ethylene glycol to form a tin solution, dissolving thiourea (CH4N2S) in a certain amount of ethylene glycol solution to form a thiourea solution, and fully mixing the tin solution and the thiourea solution to form a transparent solution; (4) then adding the transparent solution obtained in step (3) to the catalyst synthesis mother liquor obtained in step (2), and then transferring it to an autoclave, and crystallizing it at a certain temperature for a period of time; filtering and washing the solid sample with deionized water and ethanol for 5 times respectively; (5) then transferring it to a vacuum oven for drying for a certain period of time, and then transferring it to a muffle furnace for calcination.

3. The method according to claim 1 or 2, characterized in that The noble metal salt includes one or more of nitrate, chloride, and sulfate; the noble metal element includes one or more of palladium (Pd), platinum (Pt), and ruthenium (Ru).

4. The method according to claim 1 or 2, characterized in that: The concentration of the noble metal complex solution is 0.001-0.04 mol / L; the molar ratio of the noble metal to ethylenediamine in the noble metal complex solution is noble metal:ethylenediamine=1:2-10.

5. The method according to claim 1 or 2, characterized in that: The aluminum source is aluminum chloride (AlCl3), aluminum sulfate (Al2(SO4)3), sodium aluminate (NaAlO2), aluminum isopropoxide (C9H 21 AlO3) or more; The silicon source is one or more of SiO2, silicic acid, and tetraethyl orthosilicate (TEOS). The molar ratio of each component in the catalyst synthesis mother liquid is Si:Al=1:0.02-0.2, and more preferably Si:Al=1:0.03-0.1; Si:TPAOH=1:0.5-1.5, Si:H2O=1:10-25.

6. The method according to claim 2, characterized in that The molar ratio of tin to ethylene glycol in the tin solution is tin:ethylene glycol=1:10-25, the molar ratio of thiourea to ethylene glycol in the thiourea solution is thiourea:ethylene glycol=1:5-15, and the molar ratio of tin to thiourea is tin:thiourea=1:1-10.

7. The method according to claim 1 or 2, characterized in that: The crystallization temperature is 130-220° C., and the crystallization time is 10-72 hours; the calcination temperature is 450-700° C., and the calcination time is 1-10 hours.

8. The method according to claim 1 or 2, characterized in that: The amount of the noble metal in the catalyst after final calcination is 0.1-5wt%, the amount of the second component tin element is 0.1-2wt%, and the molar ratio of tin element to noble metal is more preferably tin:noble metal=1:0.1-1.

9. A noble metal-based catalyst prepared according to the method of any one of claims 1 to 8.

10. Use of the noble metal-based catalyst prepared by the method according to any one of claims 1 to 8 for degrading o-dichlorobenzene in industrial tail gas, which can achieve 100% conversion of o-dichlorobenzene pollutants in industrial tail gas within a temperature range of 350 to 400° C. and a by-product (Cl2, polychlorobenzenes) yield of less than 5%.

Citation Information

Patent Citations

  • Preparation and application of supported ruthenium catalyst with crystal plane effect

    CN110433800A

  • Method for synthesizing oxygenates by catalyzing olefin oxidation with molecular sieve supported metal catalyst

    CN118206437A

  • Platinum-based catalyst for preparing propylene through propane dehydrogenation and preparation method of platinum-based catalyst

    CN118698588A